Do Medical Students Who Participate in a Research Gap Year Produce More Research During Residency?. (May 2021) - Wright-Chisem, Joshua; Cohn, Matthew R.; Yang, JaeWon; Osei, Daniel; Kogan, Monica
Abstract : Background: The research gap year has become increasingly popular among medical students. It is also a well-known factor in consideration for orthopaedic surgery residency programs. Although medical students who participated in a research gap year typically enter residency with more research experience than their counterparts, it is unknown whether this translates to increased research productivity during residency compared with their peers. The purpose of this study was to investigate (1) whether residents who participated in a research gap year during medical school publish more peer-reviewed publications than their peers during residency, (2) whether residents who participated in a research gap year during medical school publish more first-author publications than their peers during residency, and (3) which applicant characteristics are associated with a greater number of peer-reviewed publications produced during residency. Methods: The number of peer-reviewed journal publications before and during residency was determined by querying PubMed for 81 orthopaedic surgery residents at two academic institutions. Electronic residency application service applications and curriculum vitae were reviewed to evaluate the number of conference podiums and conference posters presented before residency and during residency. The research productivity of residents who participated in a research gap year during medical school was compared with that of residents who had not participated in a research gap year. Multivariate regression was done to determine predictors of publishing peer-reviewed journal publications during residency. Results: Residents who participated in a research gap year during medical school produced more peer-reviewed journal publications during residency than those who did not (22.0 ± 20 versus 16.5 ± 20, P = 0.025). However, residents who participated in a research gap year did not produce more first-author publications compared with their peers (7.6 ± 10.0 versus 7.9 ± 7.0, P = 0.12). Residents who produced more publications before residency produced more publications while in residency (R = 0.363, P < 0.001). The United States Medical Licensing Examination step 1 score, medical school ranking, and sex were not associated with any difference in the number of journal publications produced during residency. Conclusion: A dedicated research year during medical school is associated with an increase in the number of peer-reviewed publications produced during residency. However, students who completed a research year did not publish more first-author publications than their peers. The number of publications before residency was a strong predictor of research output as a resident.